2019
DOI: 10.2478/saeb-2019-0005
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Demographic and Psychographic Segmentation to Creating Marketing Strategy of Brand Loyalty

Abstract: With growing competition, loyal customers have become the key to the company’s success. Brand loyalty has been a central structure for marketing for almost a century, yet this research topic is still modern and up to date. The aim of this contribution is to answer the research question of whether there are different segments of customers based on demographic and psychographic aspects that would differ in the level of brand loyalty in the company. In other words, do certain groups of company’s customers (accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…Another paper is focused on global research trends in sustainable digital transformation in higher education [21]. In 2021, authors focus on the research of functionalities of free available learning digital platforms in scope of selected subjects [22,23]. However, the total amount of citations is still not enough reliable to state that this topic is the hot topic of the year in scope of digitalization of education.…”
Section: Resultsmentioning
confidence: 99%
“…Another paper is focused on global research trends in sustainable digital transformation in higher education [21]. In 2021, authors focus on the research of functionalities of free available learning digital platforms in scope of selected subjects [22,23]. However, the total amount of citations is still not enough reliable to state that this topic is the hot topic of the year in scope of digitalization of education.…”
Section: Resultsmentioning
confidence: 99%
“…The use of private label is an alternative way of selling the same food products, yet potentially -a cheaper one in comparison to the traditional mechanism of buying goods from the external suppliers [27,28]. The goods sold under the private label of the retailer can be produced either by the independent manufacturers according to the franchising agreement, or by the retail chains themselves directly on the sales floor [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…These similar factors are also observed in relation to their customers, such as the demographic factors used for segmentation. For example, Gajanova et al (2019) concluded that there is a statistical dependence between age and brand loyalty, but no statistical dependence between gender and brand loyalty.…”
Section: Literature Reviewmentioning
confidence: 99%